2014
DOI: 10.1007/s12070-014-0721-7
|View full text |Cite
|
Sign up to set email alerts
|

Distortion Product Otoacoustic Emission (DPOAE) as an Appropriate Tool in Assessment of Otoprotective Effects of Antioxidants in Noise-Induced Hearing Loss (NIHL)

Abstract: Distortion product otoacoustic emission (DPOAE) appears to be an objective sensitive test of cochlear function. The aim of this study was to investigate whether DPOAE is an appropriate tool for assessment of minute changes in cochlea due to usage of antioxidant material. 48 workers exposed to continuous noise in a textile factory were randomly assigned into three groups: (1) The Control group (n = 16) received no antioxidant drugs, (2) The N-acetyl-cysteine (NAC) group (n = 16) received oral antioxidant NAC (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Although Doosti et al 24 demonstrated improvement in the amplitude of DPOAE at high frequencies (4 and 6 kHz) in both ears indicating improvement in hair cell function, they did not present enough data to document auditory threshold improvement/worsening after the use of antioxidants, or data that allowed comparison with those from the other studies, by Doosti et al 25 and Polanski and Cruz, 26 with respect to any effects on the specific frequencies of 4 and 6 kHz.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…Although Doosti et al 24 demonstrated improvement in the amplitude of DPOAE at high frequencies (4 and 6 kHz) in both ears indicating improvement in hair cell function, they did not present enough data to document auditory threshold improvement/worsening after the use of antioxidants, or data that allowed comparison with those from the other studies, by Doosti et al 25 and Polanski and Cruz, 26 with respect to any effects on the specific frequencies of 4 and 6 kHz.…”
Section: Resultsmentioning
confidence: 89%
“… Group 1 – ginkgo biloba (120 mg/day) Ginkgo biloba; α-lipoic acid + Vitamin C; Vitamin E. Ginkgo biloba (120 mg/day); α-lipoic acid (60 mg/day) + Vitamin C (600 mg/day); Vitamin E (400 mg/day) 6 months Pre- and post-pure-tone and vocal audiometry There were differences in the audiological thresholds: 500 Hz, 1000 Hz and 8000 Hz, being greater for group 4 when compared to group 2 The results before and after treatment were not significantly different in any treatment group The results did not show a statistically significant difference of the effects of antioxidant substances on the auditory thresholds of this population during the 6-month study period Group 2 – α-lipoic acid (60 mg/day) + vitamin C (600 mg/day) Group 3 – papaverine hydrochloride (100 mg/day) + vitamin E (400 mg/day) Group 4 – placebo. Doosti et al, 2014 24 Noise-induced hearing loss. Control group – no intervention Ginseng Ginseng group – 200 mg/day 14 days (2 weeks) Distortion product otoacoustic emissions – DPOAE (1, 2, 4 and 6 kHz) NAC and ginseng groups showed the result; additionally, the NAC group showed better amplitude of DPOAE than the ginseng group Reduced DPOAE amplitude at high frequencies (4 and 6 kHz) in both ears The generalization of the results found in relation to the protective effects of these interventions requires assays with different doses and in a larger population NAC group – NAC 1200 mg/day Control group N improved: Total N: 16 Ginseng group– 200 mg/day.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is important to note that mitochondrial dysfunction can extend beyond the auditory system and affect other organ systems, leading to a wide array of associated symptoms. Neurological abnormalities, such as seizures, developmental delays, and cognitive impairments, may be observed in individuals with mitochondrial hearing loss [2,5,6,[8][9][10]. Additionally, myopathy, characterized by muscle weakness and fatigue, and visual impairment, including optic atrophy and retinitis pigmentosa, can be present in syndromic disease [2,3,5,8].…”
Section: Clinical Presentationmentioning
confidence: 99%